Macroeconomic drivers of inflation expectations and inflation risk premia - Jef Boeckx; Leonardo Iania; Joris Wauters (National Bank of Belgium, 2024)
We propose a new model to decompose inflation swaps into genuine inflation expectations and risk premiums. We develop a no-arbitrage term structure model with stochastic endpoints, separating macroeconomic variables into transitory parts and long-run, economically grounded determinants, such as the equilibrium real interest rate and the inflation target. Our estimations deliver new insights into how macroeconomic variables affect market-based inflation expectation measures.
Keywords: E31; E44; E52; 330; Inflation-linked swaps; affine term structure model; inflation expectations; inflation risk premia; inflation trend; shifting endpoints